Consolidation and bank branching patterns - Avery, Robert B.; Bostic, Raphael W.; Calem, Paul S.; Canner, Glenn B. (Journal of Banking & Finance, 1999)
This paper examines the association between consolidation and changes in levels of bank branching as measured by changes in the number of bank branches per capita. Using a specially-constructed data set, we address this issue as well as how this relationship varies with the type of consolidation and initial regulatory, competitive, and market conditions. We find that merges where merging institutions have branch networks which overlap within a ZIP code (within-ZIP merger) are strongly associated with a reduction in offices per capita in that ZIP code. This result is robust across time and holds in both rural and urban areas. The findings also suggest that, contrary to popularly held views, consolidation is not unambiguously negatively associated with changes in the number of banking offices per capita. Neither within-market-but-not-within-ZIP mergers nor out-of-market mergers consistently show such a relationship. We also find that the relationships between within-ZIP and within-market-but-not-within-ZIP mergers and changes in the number of bank offices per capita are more negative in low-income neighborhoods than in other neighborhoods. However, because most states now have unrestricted branching and because savings associations are less prevalent and financially healthier than in the past, these findings may not be indicative of future branching patterns.